2021
DOI: 10.2113/2021/7866771
|View full text |Cite
|
Sign up to set email alerts
|

Morphostructural Setting and Tectonic Evolution of the Central Part of the Sicilian Channel (Central Mediterranean)

Abstract: The Plio-Quaternary tectonic evolution of the central sector of the Sicilian Channel and the resulting morphostructural setting have been analyzed using a large geophysical dataset consisting of multichannel seismic profiles, which some of them never published, and available bathymetric data. This area hosts two regional-scale tectonic domains that registered the complex pattern of deformation occurred since the Early Pliocene: (1) the Sicilian Channel Rift Zone (SCRZ), which can be divided into a western sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 78 publications
3
18
0
Order By: Relevance
“…Similar values have been reported analyzing morphological elements onshore [25]. This sector of the Sicilian Channel is affected by the Capo Granitola and Sciacca fault systems, which are part of a lithospheric-scale strike-slip fault zone running roughly N-S and crossing most of the Sicilian Channel [26][27][28]. However, this structure does not significantly influence the tectonic context of the study area since it is located about 20 km to the east of the margin of the Adventure Plateau on which we have concentrated our analyses.…”
Section: Morphology and General Geological Setting Of The Adventure P...supporting
confidence: 70%
“…Similar values have been reported analyzing morphological elements onshore [25]. This sector of the Sicilian Channel is affected by the Capo Granitola and Sciacca fault systems, which are part of a lithospheric-scale strike-slip fault zone running roughly N-S and crossing most of the Sicilian Channel [26][27][28]. However, this structure does not significantly influence the tectonic context of the study area since it is located about 20 km to the east of the margin of the Adventure Plateau on which we have concentrated our analyses.…”
Section: Morphology and General Geological Setting Of The Adventure P...supporting
confidence: 70%
“…Further support to the above interpretation is given by the fact that tectonic activity in Sardinia mainly developed from the lower-middle Pliocene to the Pleistocene, (e.g., [166][167][168]), i.e., the period during which the northward displacement of the Adventure wedge and the consequent displacement of the Alpine-Maghrebian belt were taking place. The sinistral shear here proposed in the Sicily Channel transtensional fault system is suggested by other authors (e.g., [183,184]), whereas a dextral shear is proposed in other papers (e.g., [146,153,179,[185][186][187]). However, this last hypothesis is not compatible with major pieces of evidence in the surrounding zones.…”
Section: From the Late Miocene-early Pliocene To The Late Pliocene-early Pleistocene (Reorganization Of The Tectonic Setting In The Centrmentioning
confidence: 57%
“…Such presumed kinematics would have caused compressional deformations somewhere in the Ionian zone, where instead no evidence of this effect is recognized, especially at the Syracuse escarpment, (e.g., [188]). Fur- The sinistral shear here proposed in the Sicily Channel transtensional fault system is suggested by other authors (e.g., [183,184]), whereas a dextral shear is proposed in other papers (e.g., [146,153,179,[185][186][187]). However, this last hypothesis is not compatible with major pieces of evidence in the surrounding zones.…”
Section: From the Late Miocene-early Pliocene To The Late Pliocene-early Pleistocene (Reorganization Of The Tectonic Setting In The Centrmentioning
confidence: 65%
See 1 more Smart Citation
“…This sector of the Sicilian Channel is characterized by a widespread and scattered anorogenic volcanism which occurred mainly during Quaternary, with the build up of the islands of Pantelleria and Linosa, and the formation of a series of submarine edifices located in eastern Adventure Plateau, within Graham Bank and the nearby Terrible Bank and, as recently discovered, a few nautical miles off the SW coast of Sicily (Figure 1; Calanchi et al, 1989;Rotolo et al, 2006;Civile et al, 2015;Coltelli et al, 2016;Cavallaro and Coltelli, 2019;Lodolo et al, 2019a). Part of this volcanism is related to the Pliocene rifting process that produced the grabens of Malta, Linosa, and Pantelleria (Boccaletti et al, 1987;Ben-Avraham et al, 2006;Civile et al, 2010Civile et al, , 2014Civile et al, , 2021Lodolo et al, 2012; among others), and part is linked to the presence of a NNE-trending, lithospheric transfer zone named Capo Granitola-Sciacca Fault Zone, which traverses the central sector of the Sicilian Channel (Calò and Parisi, 2014;Fedorik et al, 2017;Civile et al, 2018;Ferranti et al, 2019;Palano et al, 2020). High-resolution bathymetric data have shown that most of the volcanic centers in the Graham Bank, lying at 150-250 m water depths, are monogenetic tephra cones (Cavallaro and Coltelli, 2019) aligned with the Capo Granitola Fault System (CGFS).…”
Section: Introductionmentioning
confidence: 86%